5-S-cysteinyl-dopamine, a neurotoxic endogenous metabolite of dopamine: Implications for Parkinson's disease. (October 2019) - Badillo-Ramírez, Isidro; Saniger, José M.; Rivas-Arancibia, Selva
Abstract: Parkinson's disease (PD) is the second most common neurodegenerative disease worldwide and is characterized for being an idiopathic and multifactorial disease. Extensive research has been conducted to explain the origin of the disease, but it still remains elusive. It is well known that dopamine oxidation, through the endogenous formation of toxic metabolites, is a key process in the activation of a cascade of molecular events that leads to cellular death in the hallmark of PD. Thio-catecholamines, such as 5-S-cysteinyl-dopamine, 5-S-glutathionyl-dopamine and derived benzothiazines, are endogenous metabolites formed in the dopamine oxidative degradation pathway. Those metabolites have been shown to be highly toxic to neurons in the substantia nigra pars compacta, activating molecular mechanisms that ultimately lead to neuronal death. In this review we describe the origin, formation and the toxic effects of 5-S-cysteinyl-dopamine and its oxidative derivatives that cause death to dopaminergic neurons. Furthermore, we correlate the formation of those metabolites with the neurodegeneration progress in PD. In addition, we present the reported neuroprotective strategies of products that protect against the cellular damage of those thio-catecholamines. Finally, we discuss the advantages in the use of 5-S-cysteinyl-dopamine as a potential biomarker for PD. Highlights: Dopamine oxidation leads to the endogenous formation of toxic metabolites. 5-S-cysteinyl-dopamine is a neuroxic metabolite to dopaminergic neurons. Natural products are neuroprotectors against cell toxicity of 5-S-Cys-DA. 5-S-Cys-DA can be used as a potential biomarker for PD diagnosis.